2001
DOI: 10.1097/00006231-200101000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Thallium gated SPECT: relation between immediate post-stress evolution of ejection fraction and severity of perfusion pattern

Abstract: Good agreement exists between the severity of ischaemic perfusion pattern and LVEF degradation at stress, which is consistent with previously published data using 99Tc(m) gSPECT. Additionally, the use of 201Tl for immediate post-exercise imaging allows the observation of a physiological LVEF increase in normal and infarcted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The results of some studies using imaging modalities that diagnose ischemia on the basis of transient development of regional wall motion abnormalities or fall in global LVEF suggest that ischemic LV dysfunction manifested by global depression of LV function resolves rapidly, whereas the results of other studies indicate that regional LV dysfunction may persist [1] . Good agreement exists between the severity of ischemic perfusion pattern and LVEF degradation at stress, which is consistent with previously published data using Tc99 (m) GSPECT [2] . Post exercise wall motion abnormality (WMA) in patients with normal resting myocardial perfusion may represent prolonged post ischemic stunning, and may be related to the presence of severe angiographically confirmed coronary artery disease (CAD).…”
Section: Introductionsupporting
confidence: 91%
“…The results of some studies using imaging modalities that diagnose ischemia on the basis of transient development of regional wall motion abnormalities or fall in global LVEF suggest that ischemic LV dysfunction manifested by global depression of LV function resolves rapidly, whereas the results of other studies indicate that regional LV dysfunction may persist [1] . Good agreement exists between the severity of ischemic perfusion pattern and LVEF degradation at stress, which is consistent with previously published data using Tc99 (m) GSPECT [2] . Post exercise wall motion abnormality (WMA) in patients with normal resting myocardial perfusion may represent prolonged post ischemic stunning, and may be related to the presence of severe angiographically confirmed coronary artery disease (CAD).…”
Section: Introductionsupporting
confidence: 91%
“…Gated SPECT (G-SPECT) offers the potential advantage of combining information about myocardial function and perfusion without any extra cost, any discomfort and radiation risk to the patient [19][20][21][22][23][24]. In addition to the several previous studies, prolonged left ventricular dysfunction (WM abnormalities, LVEF and volume impairments) in post-stress G-SPECT images had been well correlated with myocardial perfusion abnormalities and degree of stenotic vessels in CAG in patients with coronary artery disease [25][26][27][28][29][30][31][32][33][34][35][36]. There are many studies in the literature that showed perfusion abnormalities in cardiac syndrome X patients using myocardial perfusion SPECT [5,6,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the decrease in stress EF depends on reversibility of perfusion defect since patients with incomplete reversible ischemia show more impaired contractility [20]. Due to an imbalance between myocardial needs and supplies, perfusion changes are first seen followed by degradation of contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we detected a significant decrease in post-stress EF to rest ([5%) in 12 of 77 (16%) patients with IMI, indicating myocardial stunning. The reported incidence of post-ischemic dysfunction ranges from 26 to 57% [6,16,[19][20][21]. These studies differ in patient selection criteria, study protocols, and definitions of myocardial stunning.…”
Section: Discussionmentioning
confidence: 99%